Design And Implementation Of A Web-Based Electronic Correspondence (E-Letter) Information System At The Regional Finance And Asset Agency of East Lampung Regency - Dika Nurdiansyah; Imam Mualim; Nuari Anisa Sivi (Politeknik Siber Cerdika Internasional, 2026)
The management of incoming and outgoing official correspondence at the Regional Finance and Asset Agency (BPKAD) of East Lampung Regency is still carried out conventionally, in which letters are recorded manually in a logbook, physically distributed between divisions, and archived in paper-based filing cabinets. This practice has led to delays in letter disposition, frequent loss or misplacement of physical documents, difficulty in tracking letter status, and inefficiency in the archiving and retrieval process. This study aims to design and implement a web-based electronic correspondence information system to digitize the administration of incoming and outgoing letters at BPKAD East Lampung Regency. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, consisting of requirements analysis, system design using Unified Modeling Language (UML), implementation using the PHP programming language with the Laravel framework and a MySQL database, and testing using the Black Box Testing method. The results show that the developed system is able to digitize the letter disposition workflow, provide real-time tracking of letter status, generate an automatic letter numbering mechanism, and produce a centralized digital archive that can be accessed based on user authorization levels. Black Box Testing on 15 functional features showed a 100% valid result, while a System Usability Scale (SUS) evaluation involving 20 respondents yielded an average score of 81.4, which is categorized as